On Leadership - Leighton , Allan; Mohan, Padam Skree Chandra (Gyan Management Journal, 2008)
Allan distills his own experience as a CEO and that of other CEO's of top British public corporations in turning round businesses from chaos and disaster · in today's turbulent times. His own experience at turning round ASDA as the COO and leading it into £3 billion Chain-store mpire and its $ 8 billion sale to Walmart and subsequent bail-out of Royalmail are fascinating stories in themselves. In the stories you also learn of queer notions & logic of CEO's which lead to disaster.
Keywords: CEO; ASDA; COO